Formulating Business Strategy for Showcar Studio - Tobing, Natasha Asmara; Toha, Moh (The Indonesian Journal of Business Administration, 2015)
Abstract - Showcar Studio is an Auto Detailing Car Saloon franchise in Indonesia. Located in Alam Sutera, Tangerang, Showcar Studio serve customers who have luxury car and motorcycle that requires premium auto detailing services. The strategy formulation process is done by analyzing the external and internal evironment to identify threats and opportunity faced by Showcar Studio with analysis method for Political, Legal, Socio-Cultural and Technology (PEST), PorterÃ¢â‚¬â„¢s five forces analysis, competitor analysis (from the external side) and analysis methods of VRIO model, business model and SWOT analysis (from the internal side). Conducted with indepth interviews to consumers about the factors that influence the decision to choose an auto detailing car saloon, then process to the Analytic Hierarchy Process (AHP) to interpret the Diamond Strategy. Diamond Strategy assist in determining companyÃ¢â‚¬â„¢s business strategy step by step to win competition in the market and resulting new business model strategy.Ã‚Â This research is aim to improve their performance in order to capture the market, increase sales, generate more profit and increase the company's competitive position.Keyword: Auto Detailing, Business Model Canvas, SWOT, AHP, Diamond StrategyÃ‚Â